Overdraft facility policy and firm's performance: an empirical analysis in Eastern European Union Industrial firms - Castillo, Leopoldo Laborda; Salem, Daniel Sotelsek (Journal of Business Economics and Management, 2013)
This article evaluates the effect of the overdraft facility (or line of credit) policy by comparing a large sample of overdraft facilitated firms and matched non-overdraft facilitated firms from Eastern Europe at sector level. The sample firms are compared with respect to rates of different performance indicators including: technical efficiency (a Data Envelopment Analysis – DEA – approach is applied to estimate technical efficiency level for individual sectors), production workers trained, expenditures of R&D, and export activity. In order to avoid the selectivity problem, propensity score matching methodologies are adopted. Results suggest that a certain level of overdraft facility given to a firm would be needed to stimulate investment in R&D, which will eventually result in growth in productivity.